TEKNIK MIXING DAN EKUALISASI AUDIO ALAT MUSIK AKUSTIK DENGAN MIC TODONG PADA PENAMPILAN YEL-YEL DALAM ACARA KUIS PAKIS BALI DI BALI TV - Sabath, Brill Obed; Darmayuda, I Komang (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
This research aims to find out how the quality of the mixing results is good and correct from the audio equalization of acoustic musical instruments with a directed mic at the Pakis Bali Quiz event. This research uses a qualitative method. The approach taken in this qualitative method is to conduct focused interviews. The data collected was obtained through observation, interviews and documentation. Then, data validation was carried out using the triangulation method and peer discussion, with the aim of ensuring that the data to be entered into the database could be explained as to the source and correctness of the data. The author analysis the data using the three activity lines proposed by Miles and Huberman, namely data reduction, data presentation, drawing conclusions/verification. From the research results, the author concluded that the audio mixing and equalization technique for acoustic musical instruments with a directed mic which was carried out during the chant performance in the Pakis Bali Quiz event on Bali TV was in line with and met the standard principles of the theories put forward by several experts regarding the technique mixing and equalizing audio for acoustic musical instruments with a directed mic. Based on the conclusions, the author provides main suggestions for upgrading equipment in terms of electrical installations.